Activation and Functional Connectivity of the Left Inferior Temporal Gyrus during Visual Speech Priming in Healthy Listeners and Listeners with Schizophrenia - Wu, Chao; Zheng, Yingjun; Li, Juanhua; Zhang, Bei; Li, Ruikeng; Wu, Haibo; She, Shenglin; Liu, Sha; Peng, Hongjun; Ning, Yuping; Li, Liang (Frontiers in Neuroscience, 2017)
Under a “cocktail-party” listening condition with multiple-people talking, healthy people, but not people with schizophrenia, can benefit from the use of visual-speech (lipreading) priming (VSP) cues to improve speech recognition. The neural mechanisms underlying the unmasking effect of VSP remain unknown. This study investigated the brain substrates underlying the unmasking effect of VSP in healthy listeners and the schizophrenia-induced changes in the brain substrates. Using functional magnetic resonance imaging, brain activation and functional connectivity for the contrasts of the VSP listening condition versus the visual non-speech priming (VNSP) condition were examined in 16 healthy listeners (27.4 ± 8.6 years old, 9 females) and 22 listeners with schizophrenia (29.0 ± 8.1 years old, 8 females). The results showed that in healthy listeners, the VSP-induced activation (against the VNSP condition) of the left posterior inferior temporal gyrus (pITG) was significantly correlated with the VSP-induced improvement in target-speech recognition against speech masking. Compared to healthy listeners, listeners with schizophrenia showed significantly lower VSP-induced activation of the left pITG and reduced functional connectivity of the left pITG with the bilateral Rolandic operculum, bilateral STG, and left insular. Thus, the left pITG and its functional connectivity are the most critical brain substrates underlying the unmasking effect of VSP, assumedly through enhancing both the processing of target visual-speech signals and the inhibition of masking-speech signals. In people with schizophrenia, the vanished unmasking effect of VSP on speech recognition is associated with a schizophrenia-related reduction of VSP-induced activation and functional connectivity of the left pITG.